Is tranexamic acid effective for all traumatic brain injury patients? a severity based systematic review and meta-analysis - Bian, Wentao; Qi, Mengxia; Ding, Lu; Lu, Yixuan; Yan, Kangling; Wang, Ziqi; Zhang, Jiancheng; Zhou, Ping (Frontiers in Pharmacology, 2025)
BackgroundThe effectiveness of tranexamic acid (TXA) in patients with traumatic brain injury (TBI) remains controversial and appears to vary with the severity of the injury. This systematic review and meta-analysis aimed to assess the impact of TXA on mortality in patients with mild to moderate TBI and severe TBI.MethodsA systematic search was conducted across PubMed, Embase, Web of Science, Cochrane Library database, Chinese CNKI database, and clinical trial repositories was conducted up to 1 May 2024. Studies comparing TXA with placebo were performed for relevant studies comparing TXA for mild to moderate and severe TBI were included. After literature screening, data were independently extracted and pooled using random-effects or fixed-effects models according to the magnitude of heterogeneity. Certainty of findings was assessed using the GRADE methodology.ResultsSixteen studies involving 15,015 patients were analyzed. TXA could significantly reduce the 28-day mortality in patients with mild to moderate TBI (RR, 0.71; 95% CI 0.60–0.85; I2 = 0%), supported by randomized controlled trials (RR: (0.74; 95% CI:0.62–0.89; I2 = 0%; high certainty) and cohort studies: (RR:0.47; 95% 0.26–0.86; I2 = 0%; low certainty). However, no mortality benefit was observed in severe TBI patients (RR, 1.05; 95% CI, 0.93–1.19; I2 = 21%), as demonstrated in RCTs (RR:0.98; 95% CI, 0.91–1.05; I2 = 0%; moderate certainty) and cohort studies (RR,1.23; 95% CI:1.08–1.4; I2 = 0%; low certainty).ConclusionThe findings suggest that the therapeutic effectiveness of TXA varies by the severity of brain injury. Post-injury administration of TXA significantly reduced 28-day mortality in patients with mild to moderate TBI (GCS: 9–15) but showed no benefit in patients with severe TBI (GCS: 3–8). Further research is needed to investigate the effect of TXA on thromboembolic events and to determine optimal dosing strategies, particularly for severe TBI patients.